Increased yolk progesterone interferes with prenatal auditory learning and elevates emotional reactivity in bobwhite quail (Colinus virginianus) chicks. Issue 2 (3rd February 2015) - Herrington, Joshua; Vallin, Claudia; Lickliter, Robert
ABSTRACT Avian eggs contain maternally derived hormones, including testosterone and progesterone. Little is currently known about the effects of these hormones on early behavioral development. We assessed the effects of elevated levels of progesterone levels on prenatal perceptual learning and postnatal emotional reactivity in Northern bobwhite quail. Prior to incubation, eggs received an injection of either progesterone (P) or oil vehicle (V). In P eggs, levels of progesterone were elevated two standard deviations above the mean based on ELISA analysis of progesterone yolk concentrations from a previous study. A third group of eggs served as controls and received no injection (C). Chicks hatched from P eggs displayed elevated levels of emotional reactivity compared to V and C chicks in a tonic immobility task and a hole‐in‐the‐wall emergence task. Chicks from P eggs also failed to demonstrate a preference for a familiarized bobwhite maternal call that had been presented prenatally. In contrast, the V and C chicks demonstrated a significant preference for the familiarized maternal call following hatching, indicating prenatal auditory learning. Our results are consistent with previous findings from precocial birds demonstrating that hormones of maternal origin can influence prenatal perceptual learning as well as emotional reactivity in the period following hatching. © 2015 Wiley Periodicals, Inc. Dev Psychobiol 57: 255–262, 2015.